MGL/SiNW-based exotic pin switch with low insertion loss and high isolation for THz communication: a quantum-rectified Schrodinger–Poisson drift-diffusion model for the design and analysis of switching behavior - Bhattacharya, Saunak; Kundu, Abhijit; Kundu, Jhuma; Sarkar, Angsuman; Mukherjee, Moumita (Advanced Optical Technologies, 2025)
In this paper, the authors explore the potential of an exotic multi-graphene layer/Si nanowire (MGL/SiNW) pin device as a switch in the THz frequency domain. The device is developed by the incorporation of multiple SiNWs into its intrinsic region. In contrast, cap and bottom layers are developed by the incorporation of multiple graphene layers. The electrical characterization of the proposed exotic pin device is carried out by developing a quantum-rectified Schrodinger–Poisson drift-diffusion (QRSP-DD) model. The developed QRSP-DD model is validated by analyzing experimental and simulation observations under similar operating conditions. After establishing its validity, the same model in conjunction with the PSpice simulator is used to obtain the switching characteristics of MGL/SiNW pin-based series-shunt and shunt single-pole single-throw (SPST), single-pole double-throw (SPDT), and single-pole multiple-throw (SPMT) switches in the THz frequency domain. The analysis proves that the MGL/SiNW pin-based SPMT switch offers low resistance (0.56 Ω), high isolation (91.15 dB), and low insertion loss (0.007 dB) at 5 THz frequency compared to its SiNW counterpart.